WORK LIFE BALANCE MENURUNKAN STRES KERJA PERAWAT - yuswandi, yuswandi; Nadirawati; Rishka Yulystiana (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
Background: Stunting is a chronic nutritional health Background: Nurses when acting as workers in hospitals with high job demands also still have a role as family members so they need a balance between work and family so they don't become stressors. Work life balance conditions and the risk of work stress on nurses are very vulnerable, especially during the Covid-19 pandemic. Objective: This study aims to determine the relationship between work life balance and work stress of nurses in the Covid-19 isolation room at Dustira Hospital Cimahi in 2021. Method:The research design was a correlation study with a total sample of 52 nurse respondents who worked in the Covid-19 isolation room using the accidental sampling technique. Collecting data using a questionnaire. Data were analysed by univariate and bivariate with Pearson product moment test. Results: The average work life balance score for nurses in the Covid-19 isolation room is 70.40 where 51.9% of respondents have a low or less balanced work life balance. The average work stress of nurses in the Covid-19 isolation room was 71.50 where 46.2% of respondents experienced high work stress. There is a low relationship between work life balance and the work stress of nurses in the Covid-19 isolation room. Conclusion: Work life balance has a strong and negative correlation with nurses' work stress. The more balanced the nurse's work life balance, the lower the work stress. d by univariate and bivariate with Pearson product moment test. Results: The average work life balance score for nurses in the Covid-19 isolation room is 70.40 where 51.9% of respondents have a low or less balanced work life balance. The average work stress of nurses in the Covid-19 isolation room was 71.50 where 46.2% of respondents experienced high work stress. There is a low relationship between work life balance and the work stress of nurses in the Covid-19 isolation room. Conclusion: Work life balance has a strong and negative correlation with nurses' work stress. The more balanced the nurse's work life balance, the lower the work stress.take. Therefore, pregnant women are expected to control their diet. Method: : This study uses a scoping review method. The databases used are EBSCOhost and PubMed with relevant search studies published from 2017-2022. The inclusion criteria of the selected articles are English articles, full text articles. The excluded articles are articles that use meta-analysis and systematic review methods. Result: 8 articles passed the selection and it was found that there were seven articles showing the type and pattern of healthy eating significantly increasing birth weight which is an indicator of growth and stunting incidence. In detail, the types and patterns of healthy eating for pregnant women are increasing food intake by 15% from usual by consuming main meals 3x a day plus 2x snacks consisting of 5 types of food (MDD-W) with 4 servings/week in each types, so that the nutrition of pregnant women is still fulfilled, complited by multivitamin supplementation (vitamin B-1 (thiamin), B-2 (riboflavin), B-6, niacin, B-12, C, and E), calcium, folic acid and tablets IFA. Conclusion: The type and pattern of healthy eating in pregnant women produces a significant good effect on birth weight to prevent stunting. And demographic factors affect the diet of pregnant women.